Performance and theatricality in the poetry of C.P. Cavafy - Pappas, A (2019)
The close relationship between Cavafy and theatre has been widely established. While previous research has comprehensively detailed the inspiration Cavafy has taken from writers and themes of ancient theatre, very little work has been conducted on Cavafy’s use of performance and theatre as a whole. The aim of my thesis is to explore how the poetry of Cavafy is informed by theatre and performance, and how these modes are used to subvert and create identities. In addition, theatre and performance are rarely fixed quantities in Cavafy’s poetry; instead, they are fluid and can mean a variety of ideas. Theatre, for example, can refer to a building, an event, a code, or a practice. In turn, this means that the way performance and theatre inform Cavafy’s poetry is often about the idea of the ‘in-between’ that is so central to his work. Things are rarely black-and-white, and the grey areas are where the interest lies. In support of my position, I firstly summarise existing studies on Cavafy and theatre, as well as the references or observations made on Cavafy’s dramatic nature or theatricality. In the first chapter, I conduct a comprehensive overview of published literature on Cavafy’s work and his interactions with the world of theatre. My review shows that the bibliography of work detailing Cavafy and theatre may be reasonably extensive, but most scholars approach his work from from a text-centric perspective – that is, the ways in which Cavafy used theatrical texts as inspirations for poems, rather than from the point of view of performance. I conclude that, though much has been written on theatre as source material for Cavafy, not enough critical analysis has focused on how theatricality and performance permeate his body of work as a whole. This introduction chapter summarizes the existing landscape of literature on Cavafy and performance, highlights the limitations of existing studies, and identifies an important gap in our existing understanding of Cavafy’s poetry. These observations form the rationale for my original analysis, which begins in the next chapter. I begin my original analysis by introducing the dramatic devices utilised by Cavafy in his poetry, and establishing definitions of theatre, drama, and performance for the purposes of this thesis. The specific dramatic devices I examine in Cavafy’s work include staging, props, lighting, sound, explicit mentions of theatre (as a building, activity, institution, or art form) or theatrical events, dialogue, monologue, actors, and spectators, and finally, text, direction, and set design. I use these throughout the thesis to clarify the way Cavafy engages with memory, history, identity, and other such themes from a theatrical point of view. I define theatricality as the inherent theatre of every-day life and drama as the way in which Cavafy acts as a stage director, developing scenes and narration in his poems. I define performance in accordance with the emergence of performance studies; in other words, it encompasses not only theatrical performances, but also rituals, ceremonies, public events and performativity.